PATH-30. CLINICAL AND GENETIC CHARACTERISTICS OF HISTONE H3 K27M-MUTANT DIFFUSE MIDLINE GLIOMAS IN ADULTS. (9th November 2020) - Schulte, Jessica; Buerki, Robin; Lapointe, Sarah; Molinaro, Annette; Zhang, Yalan; Villanueva-Meyer, Javier; Perry, Arie; Phillips, Joanna; Tihan, Tarik; Bollen, Andrew; Pekmezci, Melike; Butowski, Nicholas; et al.
Abstract: BACKGROUND: "Diffuse midline glioma, H3 K27M-mutant" is a new tumor entity established in the 2016 WHO Classification of Tumors of the CNS that comprises a set of diffuse gliomas arising in midline structures that is molecularly defined by a recurrent K27M mutation in genes encoding the histone 3 variants H3.3 or H3.1. While this tumor entity is associated with poor prognosis in children, clinical experience in adults remains limited. Given the more frequent origin in the thalamus or spinal cord in adults versus the brainstem in children, gliomas with this mutation may encompass a heterogeneous population of tumor subtypes that vary based on patient age, anatomic site of origin, and concurrent genetic alterations. METHODS: The 60 patients included were 18 years or older at initial diagnosis, during the period of 2014-2019 at UCSF. Cases were identified using immunohistochemistry with a H3 K27M-mutant specific antibody and/or next-generation sequencing of histone 3 genes H3F3A, HIST1H3B and HIST1H3C . Targeted NGS was performed on tumors from 21 patients, utilizing an UCSF institutional panel or a variety of commercial sources. RESULTS: Patients presented primarily in the 3 rd decade of life, and 57% of tumors were located in the thalamus. Genomic profiling revealed p.K27M mutations exclusively in H3F3A and an absence of mutations in HIST1H3B or HIST1H3C, which are present in approximately one-third of pediatric diffuse midline gliomas. Additionally, these adult H3 K27M-mutant diffuse midline gliomas are universally IDH-wildtype, and have frequent mutations in TP53, PPM1D, FGFR1, NF1, and ATRX . The overall survival of this adult cohort is longer than historical averages for both H3 K27M-mutant diffuse midline glioma in children and IDH-wildtype glioblastomas in adults. CONCLUSIONS: Together, these findings indicate that H3 K27M-mutant diffuse midline glioma represents a heterogeneous disease with regard to outcomes, sites of origin, and molecular pathogenesis in children versus adults.